The Ethical Experience of Online Journalists in Avoiding Trial by the Press - Wahyudi, Dicky; Sujoko, Anang (Journalism Study Program, Faculty of Communication Sciences, Universitas Padjadjaran, 2024)
Trial by the press is an ethically prohibited practice in journalism activities in Indonesia. However, it still occurs in various online media, meaning that there is something wrong with the ethical actions of online media journalists. This research aims to reveal the ethical experiences of online media journalists in avoiding trial by the press. This research method uses a phenomenological approach by conducting interviews with five online media journalists and a literature study of regulatory trials by the press in Indonesia. The results show that trial by the press has been institutionally regulated to be avoided by journalists, especially in Law 40/1999, Journalistic Code of Ethics from the Press Council, PWI, and AJI. However, journalistic ethical principles in institutional regulations are no longer compatible with the working mechanisms of online media, thus creating a dilemma for online media journalists to choose between the two. However, online media journalists do not view institutional regulations and online media working mechanisms as dualism in the practice of online journalism. Their experience in elaborating institutional regulations and online media working mechanisms can minimize the occurrence of trials by the press. We concluded that contextual and situational elaboration of institutional regulations and working mechanisms of online media can produce an authentic meaning for journalists to avoid trial by the press in online media.